2009
DOI: 10.1002/jrs.2475
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex identification of bacteria in bacterial mixtures with surface‐enhanced Raman scattering

Abstract: Surface-enhanced Raman scattering (SERS) is a technique capable of identifying each component in a mixture because of itsintrinsically narrow spectral bands. In a clinical setting, the identification of bacteria from its initial culture by collecting the colonies on the culture plate significantly decreases the analysis time and the cost. The identification of bacteria from their mixtures is attempted using SERS. A simple mixing procedure of bacterial samples and concentrated colloidal suspension is proven to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The suspended bacteria were washed three times by centrifugation for 5 min at 7500 rpm. Then, 10 7 bacteria were seeded onto half of 9 different nutrient agar plates, and each plate was incubated for different hours (1,2,4,6,8,10,12,18, and 24 h). At each specific time, bacteria were collected with either loop or spatula.…”
Section: Preparation Of Bacteria Samples For Sers Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suspended bacteria were washed three times by centrifugation for 5 min at 7500 rpm. Then, 10 7 bacteria were seeded onto half of 9 different nutrient agar plates, and each plate was incubated for different hours (1,2,4,6,8,10,12,18, and 24 h). At each specific time, bacteria were collected with either loop or spatula.…”
Section: Preparation Of Bacteria Samples For Sers Measurementsmentioning
confidence: 99%
“…As explained in the experimental section, nine different time points (1,2,4,6,8,10,12,18, and 24 h) during growth of seven different bacteria species were selected for spectral acquisition. For the sake of the manuscript length, we here show spectra of the bacteria at 4 different time points (1, 6, 12, and 24 h) in Fig.…”
Section: Sers Investigation Of Spectral Changes Of Bacteria During Thmentioning
confidence: 99%
See 1 more Smart Citation
“…The average size of the silver colloid nanoparticles was about 35-40 nm. Other studies [33,34] demonstrated a similar diameter of silver nanoparticles produced by the same method.…”
Section: Discussionmentioning
confidence: 55%
“…The identification and discrimination of bacterial mixtures were investigated. [21] In order to demonstrate the effectiveness of the approach, we have constructed a 3D plot of Euclidean distances calculated using the 10 SERS spectra of each yeast, bacteria species and their mixtures. The 3D plot is seen in Fig.…”
Section: Resultsmentioning
confidence: 99%